Fungal Biotechnology of the Red Sea Alga Sarggassum subrepandum with Potential of Anticancer and Anti-Hepatitis C Virus Protease Activities - W. Hawas, Usama; Al-Farawati, Radwan; T. Abou El-Kassem, Lamia; F. Ahmed, Eman (Letters in Organic Chemistry, 2017)
Background: Marine algal-derived endophytic fungi have attracted considerable attention in the recent decade due to their prolific production of structurally diverse secondary metabolites with various biological activities. In this study, the potential inhibition of endophytic fungi isolated from Red Sea brown alga Sargassum subrepandum was examined against HCV protease enzyme. Methods: An in vitro HCV NS3-4A protease assay was used to evaluate the HCV protease inhibition activity of the fungi. The fungus with a high-level inhibition was identified based on 18S rDNA and further subjected to chemical and biological investigations on its secondary metabolites. Results: The endophytic fungal strains, Aspergillus parasiticus, Aspergillus terreus and Geotrichum candidum were isolated from Red Sea brown alga Sargassum subrepandum. Of the three fungi, Aspergillus terreus had the highest HCV protease inhibition activity (IC50 10 μg/mL). From that fungus, eleven compounds were isolated and their structures were elucidated on the basis of NMR and MS spectroscopic analysis. Moreover, sophisticated 2-dimensional NMR spectroscopy of the isolated symmetric diketopiperazine bisdethiodi(methylthio)acetylaranotin has been recorded. Of the compounds in the A. terreus extract, only bisdethiodi(methylthio)acetylaranotin and cyclo(L-Tyr-L-Pro) were shown to have a potent HCV PR inhibition with IC50 13.0 and 18.2 μM, respectively. Conclusion: The present study shows that the organic extract of A. terreus has a potential HCV protease inhibition activity. These preliminary results are of great interest and can be proposed for new candidate of anti-HCV agents.
Keywords: HCV N3/4A protease